2019
DOI: 10.2478/aut-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Characteristic Impedance of Textile Signal Lines While Mechanically Loaded

Abstract: The paper presents studies over the changes in the characteristic impedance of selected type of textile signal lines (TSLs) during mechanical loads. The article describes the construction of tested lines, the measurement method, and statistical analysis of the collected results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The plan of dividing the TSLs into groups was to include in each of the three subgroups at least five different lines. Also, the substrates had three specified weaves: plain, twill, and satin, and then all TSL were divided into three groups of the specified weave, the same method used earlier in [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plan of dividing the TSLs into groups was to include in each of the three subgroups at least five different lines. Also, the substrates had three specified weaves: plain, twill, and satin, and then all TSL were divided into three groups of the specified weave, the same method used earlier in [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The value of the TSL characteristic impedance depends mainly on the geometrical dimensions of such elements, the dielectric properties of the substrate and the resistance of the material from which the electrically conductive paths were made. Earlier, only straight TSLs were made and tested [ 20 ]. In a straight signal line, the electro-conductive paths are in the form of straight lines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests consisted of stretching the tested lines with a specified force and measuring the impedance profile after this stretching. As a result of the research, they [24] found that the tensile forces reduced the characteristic impedance of the line. They also found that the lines made of fabrics with a satin weave had the smallest impedance change under the influence of force loading.…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, these are very important issues because such lines should work properly not only in laboratory conditions but also in regularly used smart textiles. Lesnikowski and Kubiak [24] studied the changes in the characteristic impedance of selected types of TSLs during mechanical loading. These tests consisted of stretching the tested lines with a specified force and measuring the impedance profile after this stretching.…”
Section: Introductionmentioning
confidence: 99%